Long Non-Coding RNAs H19 and HOTAIR Implicated in Intervertebral Disc Degeneration - Wang, Zhun; Zhang, Jingwei; Zheng, Wei; He, Yongjin (Frontiers in Genetics, 2022)
Objective: Intervertebral disc degeneration (IDD) is the major cause of low back pain. We aimed to identify the key genes for IDD pathogenesis. Methods: An integrated analysis of microarray datasets of IDD archived in publicly Gene Expression Omnibus was performed. Bioinformatics analyses including identification of differentially expressed mRNA/microRNA/long non-coding RNAs (DEMs/DEMis/DELs), pathway enrichment and competitive endogenous RNA (ceRNA) network construction were performed to insight into the potential functions of differentially expressed genes (DEGs). The diagnostic value of DEMis in distinguishing IDD from normal controls was evaluated through receiver operating characteristic (ROC) analysis. Results: DEGs were identified in IDD, including H19 and HOTAIR. In DEMis-DEMs network of IDD, miR-1291, miR-4270, miR-320b had high connectivity with targeted DEMs. Cell death biological processes and JAK-STAT pathway were significantly enriched from targeted DEMs. The area under the curve (AUC) of 10 DEMs including miR-1273e, miR-623, miR-518b, and miR-1291 in ROC analysis were more than 0.8, which indicated that those 10 DEMs had diagnostic value in distinguishing IDD from normal individuals. Conclusions: DELs H19 and HOTAIR were related to IDD pathogenesis. Cell death biological processes and JAK-STAT pathway might play key roles in IDD development.